2012
DOI: 10.1002/jpln.201200012
|View full text |Cite
|
Sign up to set email alerts
|

Gaseous emissions of nitrogen and carbon from urban vegetable gardens in Bobo‐Dioulasso, Burkina Faso

Abstract: Urban and peri-urban agriculture (UPA) is an important livelihood strategy for the urban poor in sub-Saharan Africa and contributes to meeting increasing food demands in the rapidly growing cities. Although in recent years many research activities have been geared towards enhancing the productivity of this land-use system, little is known about turnover processes and nutrient efficiency of UPA. The aim of our study therefore was to determine horizontal fluxes of N, P, K, and C as well as gaseous N and C emissi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 30 publications
(17 citation statements)
references
References 31 publications
1
15
1
Order By: Relevance
“…The "Tomato scenario" corresponds to the average of six tomato cropping systems from urban gardens in West Africa for which no field emissions data were available. The "Rotation scenario" corresponds to 25 % of the average of four annual rotations from urban gardens in West Africa (Predotova et al 2010(Predotova et al , 2011Lompo et al 2012). Our study shows large surplus comparable to the literature.…”
Section: Intensive Fertilization Management: Important N and P Surplusessupporting
confidence: 82%
See 1 more Smart Citation
“…The "Tomato scenario" corresponds to the average of six tomato cropping systems from urban gardens in West Africa for which no field emissions data were available. The "Rotation scenario" corresponds to 25 % of the average of four annual rotations from urban gardens in West Africa (Predotova et al 2010(Predotova et al , 2011Lompo et al 2012). Our study shows large surplus comparable to the literature.…”
Section: Intensive Fertilization Management: Important N and P Surplusessupporting
confidence: 82%
“…Regarding fertilizers, large quantities of nutrients in the form of chemical fertilizers and livestock manure are applied to urban gardens Sangare et al 2012). Due to low yields, an important part of nutrient input is lost to the environment (Predotova et al 2010(Predotova et al , 2011Lompo et al 2012). Nutrient emissions such as NH 3 , N 2 O, NO 3 , and phosphorus often contribute considerably to the environmental risk associated to urban cropping systems.…”
Section: Introductionmentioning
confidence: 99%
“…Greenhouse gas emissions are the main reasons of global warming, which caused extreme weather disasters happened frequently all over the world in the past 10 years [1,2]. Previous studies have shown that agricultural-source greenhouse gas emissions account for about 14% of the global greenhouse gas emissions caused by human activities.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown that agricultural-source greenhouse gas emissions account for about 14% of the global greenhouse gas emissions caused by human activities. Furthermore, the ratio shows an increasing trend and N 2 O (one of the greenhouse gas) released into atmosphere from soil might increase 26% from 2011 to 2020 [2].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation